2022
DOI: 10.1021/acs.orglett.2c01389
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Chiral Diazocine Derivatives via a Copper-Catalyzed Dearomative [5+3] Cycloaddition

Abstract: Copper-catalyzed [5+3] cycloaddition of N-aromatic zwitterions and enol diazoacetates produced enantio-enriched diazocine derivatives. A sterically encumbered BOX ligand and NaBArF additive played significant roles in driving the overall catalytic process via the unfavorable dearomatization to construct the desired eight-membered heterocyclic compounds. The induced stereoselectivity was preserved after further modifications of the skeleton, which demonstrates the potential applications of the developed asymmet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…Very recently, the same authors found that copper­(I) chloride catalyzed an enantioselective (5 + 3) cycloaddition of quinolinium zwitterions 131 and enol diazoacetates 122 in the presence of a sterically encumbered chiral BOX-type ligand and NaBArF as a crucial additive (Scheme ). In this manner, enantioenriched diazocine derivatives 147 were obtained in very good yields and enantiomeric excesses. Substituents at the C4–C7-positions of the quinolinium ring, irrespective to their electronic properties, were tolerated in the cycloaddition process, as well as several aryl substituents on the enamide moiety.…”
Section: Cycloaddition Reactions and Annulationsmentioning
confidence: 99%
“…Very recently, the same authors found that copper­(I) chloride catalyzed an enantioselective (5 + 3) cycloaddition of quinolinium zwitterions 131 and enol diazoacetates 122 in the presence of a sterically encumbered chiral BOX-type ligand and NaBArF as a crucial additive (Scheme ). In this manner, enantioenriched diazocine derivatives 147 were obtained in very good yields and enantiomeric excesses. Substituents at the C4–C7-positions of the quinolinium ring, irrespective to their electronic properties, were tolerated in the cycloaddition process, as well as several aryl substituents on the enamide moiety.…”
Section: Cycloaddition Reactions and Annulationsmentioning
confidence: 99%
“…In 2022, Yoo's group explored the efficient methods for the synthesis of fused eight-membered N-heterocyclic compounds 119 (Scheme 25b). 52 In this transformation, quinolinium 1,4-zwitterions 24 were employed to react with enol diazoacetates 118 . Under the catalysis of CuCl, ligand L1 and sodium tetrakis[3,5-bis(trifluoromethyl)phenyl]borate (NaBArF), the reaction proceeded smoothly to give a wide range of chiral diazocine derivatives 119 in moderate to excellent yields with enantioselectivities.…”
Section: Cyclization Reactions Of Pyridinium 14-zwitterions and Pyrid...mentioning
confidence: 99%
“…Yoo et al also described a stereoselective (5 + 3) cyclization between quinolinium 1,4-zwitterions 2′ and enol diazoacetates 169 , catalyzed by Cu(I), as shown in Scheme 37 [ 109 ]. The desired diazocine derivatives ( S )- 173 could be synthesized in excellent yields (up to 97%) with perfect ee values (up to 97%) using a Cu(I)/bisoxazoline ligand L2 complex as a catalyst and a catalytic amount of NaBArF as an additive.…”
Section: Nitrogen-based Pyridinium and Quinolinium 14-zwitterionsmentioning
confidence: 99%